The Effects of Perceived Coach Leadership on Athlete’s Burnout: Implications for Quality of Coach-Athlete Relationship - Chrissel Jay Duhaylungsod; Kate Icalina; Jet Clayton Longakit (CV. FOUNDAE, 2025)
Background: Numerous studies have explored the effect of coach-athlete relationships on athletes' burnout, yet there has been a notable gap in the mediating role of coach leadership.Aim: This study sought to investigate how perceived coach leadership affects athlete burnout and its implications for the quality of coach-athlete relationships.Methods: A total of 248 athletes from individual, dual, and team sports participated, comprising 142 (57.26 percent) males and 106 (42.74 percent) females, aged between 18 and 35 years (M= 20.24, SD = 2.02), all based in Iligan City. The study examined the variables and their connections by employing a descriptive-correlational methodology. The researchers utilize a snowball sampling technique to expand the sample through referrals.Results: The findings revealed that coach leadership does not directly mediate the relationship between the coach-athlete dynamic and athlete burnout. However, the quality of the coach-athlete relationship significantly impacts burnout. Key relationship factors, such as emotional closeness, complementarity, and commitment, play crucial roles. Athletes who reported stronger relational bonds with their coaches, characterized by trust, open communication, and shared goals, experienced lower levels of burnout. Conversely, weaker relationships, marked by conflict or lack of emotional connection, were linked to higher burnout levels. Conclusion: While coach leadership does not serve as a mediator, it plays a vital role in fostering a supportive coach-athlete relationship, significantly reducing burnout. This study emphasizes the significance of fostering robust relationships between coaches and athletes to reduce athlete burnout. Sports coaches should prioritize relationship-building over merely employing leadership skills since this can significantly enhance an athlete's emotional resilience and mental well-being. Coaches must emphasize cultivating closeness with athletes by promoting open communication, trust, and empathy.